PENGEMBANGAN USAHA PRODUKSI MAKANAN OLAHAN RINGAN DI DESA CURAH COTTOK SITUBONDO JAWATIMUR - Andrew Joewono; Rasional Sitepu; Lanny Agustine; Tarsisius Dwi Wibawa Budianta; Indah Kuswardani; Nekhasius Agus Sunarjanto; Suratno Suratno (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Business development to increase the income of MSME actors by taking into account the potential of the village. Business development in the form of the production of corn chips snack food, raw materials in the form of corn have been produced on village-owned agricultural land and have been harvested, this is strongly supported by agricultural products from the area so that the development of a light processed food business is very feasible to do, so training is needed to make a business plan, which in the end is expected to improve the welfare of business actors